Investigating the impact of initial soil moisture conditions on total infiltration by using an adapted double-ring infiltrometer. Issue 7 (18th May 2016) - Ruggenthaler, Romed; Meißl, Gertraud; Geitner, Clemens; Leitinger, Georg; Endstrasser, Nikolaus; Schöberl, Friedrich
ABSTRACT: This study presents an adaptation of the double-ring infiltrometer (DRI) device, which allows several infiltration experiments to be conducted at the same location. Hence, it becomes possible to use the DRI method to investigate infiltration behaviour under different initial soil moisture conditions. The main feature is the splitting of the inner ring into two parts. While the lower part remains in the soil throughout the investigation period, the upper part is attached to the lower one just before the infiltration experiment. This method was applied to eight test sites in an Alpine catchment, covering different land-use/cover types. The results demonstrated the applicability of the adapted system and showed correlations between total water infiltration and initial soil moisture conditions on pastures, independent of the underlying soil type. In contrast, no correlation was found at forest sites or wetlands. Thus, the study emphasizes the importance of paying special attention to the impact of initial soil moisture conditions on the infiltration—and consequently the runoff behaviour—at managed areas. Given the differences in the total infiltrated water of between 30 and 1306 mm, consideration of the interplay between initial soil moisture conditions, land-use/cover type, and soil properties in rainfall–runoff models is a prerequisite to predict runoff production accurately.EDITOR Z.W. Kundzewicz;ASSOCIATE EDITOR not assigned